2013
DOI: 10.1001/jamaneurol.2013.3205
|View full text |Cite
|
Sign up to set email alerts
|

Anti–N-Methyl-d-Aspartate Receptor Encephalitis

Abstract: steroids, IVIg, and rituximab, both the serum and CSF antibody titers fell. With additional immunomodulatory treatment, the antibody levels were unchanged.The patient had 11 magnetic resonance imaging scans of the brain during her hospitalization. With time, there was progressive atrophy, with parenchymal loss and ventricular dilation. ARTICLE INFORMATION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Regarding second-line immunotherapies, this evidence synthesis showed a striking association of rituximab administration with monophasic course, with 5.9-fold reduced odds of relapse after 24 months or more follow-up, also confirmed across all the major age groups in univariate analyses (eTable 9 in the Supplement). Our review also showed the emerging use of escalation second-line therapies, such as intravenous/intrathecal methotrexate, subcutaneous/intravenous bortezomib, and intravenous tocilizumab, in a very limited subset of patients (eTable 4 in the Supplement), insufficient for inclusion in our multivariable modeling . Their efficacy and safety in NMDARE warrant further investigation .…”
Section: Discussionmentioning
confidence: 86%
“…Regarding second-line immunotherapies, this evidence synthesis showed a striking association of rituximab administration with monophasic course, with 5.9-fold reduced odds of relapse after 24 months or more follow-up, also confirmed across all the major age groups in univariate analyses (eTable 9 in the Supplement). Our review also showed the emerging use of escalation second-line therapies, such as intravenous/intrathecal methotrexate, subcutaneous/intravenous bortezomib, and intravenous tocilizumab, in a very limited subset of patients (eTable 4 in the Supplement), insufficient for inclusion in our multivariable modeling . Their efficacy and safety in NMDARE warrant further investigation .…”
Section: Discussionmentioning
confidence: 86%
“…42-44 Other escalation treatments have been reported in the literature, such as IV/intrathecal methotrexate with intrathecal corticosteroids and subcutaneous/IV bortezomib; these have more limited evidence, but can be used according to the local treating center's expertise. 41,43-57…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Other escalation treatments have been reported in the literature, such as IV/intrathecal methotrexate with intrathecal corticosteroids and subcutaneous/IV bortezomib; these have more limited evidence, but can be used according to the local treating center's expertise. 41,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] The patient who has severe disease and is failing to improve remains a major challenge. The clinician needs to balance the risk of severe disease (such as being on the intensive care unit) with the risk of treatment side effects, in the knowledge that NMDARE symptoms may take many weeks or months to improve.…”
Section: Tocilizumabmentioning
confidence: 99%
“…Case reports occasionally describe reduction [ 6 , 22 , 26 , 32 ] or eradication [ 33 , 34 ] of NMDAR Abs in serum following first-line immunotherapy in patients with good outcome, with concomitant decrease in CSF titers [ 6 , 22 , 26 , 32 34 ]. Reductions in CSF titers with second-line treatments have also been demonstrated [ 31 , 35 , 36 ], but for obvious practical reasons CSF titers are not widely available in patients who have improved. Successful aggressive immunosuppression with intrathecal MTX and intravenous (IV) alemtuzumab was reported in 4 children [ 37 , 38 ], 2 of whom were refractory to prolonged immunotherapy, including cyclophosphamide and/or rituximab.…”
Section: N -Methyl D-aspartate Receptormentioning
confidence: 99%